Taqui Qosqo Sayhua. Espacio, sonido y ritmo astronómico en la concepción simbólica del Cusco incaico - Gudemos, Mónica (Revista Española de Antropología Americana, 2008)
The socialization of the high region of the Cusco Valley, which understands like sacred territory of the Inca elite, was periodically actualized according to a complex net of administrative relations and calendar obligations, organized into a yearly sequence of ceremonial circuits. These circuits, true «institutional choreographies», were spatially articulated from a social conception of the topographical profile, in which the mountains were considered not only natural landmarks of the territories administrated by the different social groups and horizon referent points for the astronomical observations, but also landmarks for the ritual contention and isolation of the elite space. In this paper we treat this articulation through the dynamic of socialization of the Inti Raymi, one of the principal Inca feasts; precisely from the conceptual unit «space-sound-astronomic rhythm» subjacent in their ceremonial structure.